2008
DOI: 10.1111/j.1365-2486.2008.01548.x
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of respiration, nitrogen, and sugars underlies convergent temperature acclimation in Pinus banksiana across wide‐ranging sites and populations

Abstract: Patterns and mechanisms of short-term temperature acclimation and long-term climatic adaptation of respiration among intraspecific populations are poorly understood, but both are potentially important in constraining respiratory carbon flux to climate warming across large geographic scales, as well as influencing the metabolic fitness of populations. Herein we report on leaf dark respiration of 33-year-old trees of jack pine (Pinus banksiana Lamb.) grown in three contrasting North American common gardens (0.9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(154 citation statements)
references
References 64 publications
10
139
1
4
Order By: Relevance
“…Previous studies have shown that plant photosynthesis and GPP can acclimate to temperature change via an increase in optimum temperature in a warmer environment (Mooney et al, 1978;Baldocchi et al, 2001;Niu et al, 2008). It has also been documented that R e responds exponentially to temperature as long as there is no soil water limitation (Law et al, 1999), and its temperature sensitivity (Q 10 ) decreases in a warmer environment, a process also described as temperature acclimation (Lloyd & Taylor, 1994;Luo et al, 2001;Tjoelker et al, 2008;Piao et al, 2010). The temperature acclimation of either GPP or R e can lead to changes in the temperature response of NEP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that plant photosynthesis and GPP can acclimate to temperature change via an increase in optimum temperature in a warmer environment (Mooney et al, 1978;Baldocchi et al, 2001;Niu et al, 2008). It has also been documented that R e responds exponentially to temperature as long as there is no soil water limitation (Law et al, 1999), and its temperature sensitivity (Q 10 ) decreases in a warmer environment, a process also described as temperature acclimation (Lloyd & Taylor, 1994;Luo et al, 2001;Tjoelker et al, 2008;Piao et al, 2010). The temperature acclimation of either GPP or R e can lead to changes in the temperature response of NEP.…”
Section: Introductionmentioning
confidence: 99%
“…Like photosynthesis, respiratory acclimation is more marked in leaves that develop at the new temperature (Campbell et al, 2007). Several factors contribute, including the general increase in protein content (Atkin et al, 2005(Atkin et al, , 2008Campbell et al, 2007;Tjoelker et al, 2008) and changes in the activities or levels of specific respiratory enzymes, in particular alternative oxidase and uncoupling protein (Armstrong et al, 2007;Campbell et al, 2007). Respiration is often subdivided into growth respiration (R g ) and maintenance respiration (R m ; Penning de Vries et al, 1974;Amthor, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of climate drought on the temperature sensitivity of vegetation growth, however, may be partly alleviated by CO 2 -induced increase in vegetation water use efficiency 11,12 . In addition, some species can also gradually adjust to continuous warming by acclimation of their physiological responses (for example, through their rates of photosynthesis and autotrophic respiration) [13][14][15] . These issues all lead to the question of how and where has the impact of temperature on vegetation productivity changed over the last three decades?…”
mentioning
confidence: 99%